2018
DOI: 10.1111/conl.12622
|View full text |Cite
|
Sign up to set email alerts
|

Rise and fall of forest loss and industrial plantations in Borneo (2000–2017)

Abstract: The links between plantation expansion and deforestation in Borneo are debated. We used satellite imagery to map annual loss of old‐growth forests, expansion of industrial plantations (oil palm and pulpwood), and their overlap in Borneo from 2001 to 2017. In 17 years, forest area declined by 14% (6.04 Mha), including 3.06 Mha of forest ultimately converted into industrial plantations. Plantations expanded by 170% (6.20 Mha: 88% oil palm; 12% pulpwood). Most forests converted to plantations were cleared and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(120 citation statements)
references
References 18 publications
5
99
0
2
Order By: Relevance
“…Oil palm and timber plantations covered 75,480 km 2 on Borneo in 2010, equivalent to 10% of the island's land area (Gaveau, Sloan, et al, ). From 2000 to 2017, the area of industrial plantations on Borneo is estimated to have increased by 170% (6.2 Mha), of which 88% can be attributed to palm oil expansion, with 3.06 Mha of forest converted to plantation (Gaveau et al, ). Two thirds of the Borneo forest area lost to plantations between 1973 and 2015 had been selectively logged prior to conversion (Gaveau, Sloan, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oil palm and timber plantations covered 75,480 km 2 on Borneo in 2010, equivalent to 10% of the island's land area (Gaveau, Sloan, et al, ). From 2000 to 2017, the area of industrial plantations on Borneo is estimated to have increased by 170% (6.2 Mha), of which 88% can be attributed to palm oil expansion, with 3.06 Mha of forest converted to plantation (Gaveau et al, ). Two thirds of the Borneo forest area lost to plantations between 1973 and 2015 had been selectively logged prior to conversion (Gaveau, Sloan, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Li, ), partly through engagement with global demand for commodities. The most prominent such example is palm oil, which has led to the rapid expansion of oil palm plantations across Borneo and Sumatra over the past two decades (Gaveau et al, ). Although the widespread claim that oil palm cultivation is the leading cause of deforestation and orangutan extinction in these areas is debatable (see, e.g., Ancrenaz, Meijaard, Wich, & Simery, , table 1), its expansion has had significant implications for orangutan survival: habitat loss, degradation and fragmentation, as well as increased incidences of human–orangutan conflict.…”
Section: Key Concerns and Challenges: A Synthetic Discussionmentioning
confidence: 99%
“…Gingold (2010) reported that many millions of hectares of Indonesia would fit the criteria of degraded lands. To clarify these criteria, the Rosoman et al (2017) group, comprised of industry and NGO, produced the High Carbon Stock (HCS) Approach Toolkit, for maintaining carbon stock and managing GHG's, which provides guidelines on assessing carbon stock and managing the carbon inventory ( Figure 5). Taking this approach further, the Environmental Defence Fund (Miller and Cai, 2015) have proposed Zero Deforestation Zones in Indonesia, but also recommend meeting future palm oil needs through intensification of production and expansion onto degraded lands.…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%
“…Source: Rosoman et al (2017). Given oil palm is grown as a cash crop and used for a wide range of purposes, the impact of cultivation on standing biomass is only part of the story.…”
Section: Greenhouse Gas Emissionsmentioning
confidence: 99%